Transcriptional analysis and immunological characterization of iron uptake receptors of shigella flexneri 2a USM clinical isolates - Ismail, Che Muhammad Khairul Hisyam (2022)
Shigellosis is a public health concern disease with high mortality and morbidity rate, especially among children under the age of five. Without proper care, the disease worsens from watery stool to acute bloody diarrheal. The rise of multi-drug resistance strain in most gram-negative bacteria including Shigella species limits the current clinical treatment as most of the antibiotic administrated is less effective. Besides the unavailability of commercial or approved vaccines against shigellosis disease and the report of the predominant shift from Shigella flexneri to Shigella sonnei, the development of an effective and long-protection vaccine is urgently needed. Most current developed vaccines are reported to cause side effects such as dysentery and the protection efficacy varies among vaccinated individuals at different groups of ages. In view of this, a comprehensive understanding of molecular pathogenesis among infected individuals is of the utmost importance. Interestingly, iron molecules have been known to play a critical role in bacterial survival and virulent determinant by upregulation of multiple iron uptake receptor proteins within the infected individuals to acquire enough iron sources. In this study, both of S. flexneri 2a Hospital USM clinical isolates (SH057 and SH062) were grown under the presence of 200 μM of 2,2- bipyridyl. The expression of gene encoding iron uptake receptors of S. flexneri 2a, fepA, fhuA, IutA, efeU, and SitA were observed by quantitative polymerase chain reaction (qPCR). All iron uptake receptors of S. flexneri 2a were further analyzed by using the bioinformatic approach to further screening the potential target vaccine candidates against shigellosis disease. The selected iron uptake receptors then proceeded for construction of recombinant protein and predict the antigenicity of the recombinant protein corresponding to iron uptake receptors using dot-blot and ELISA approach. The qPCR result showed the expression rate of majority iron uptake receptors including fepA, fhuA, IutA, efeU, and sitA of both virulent (SH057) and mild virulent (SH062) of S. flexneri 2a clinical isolates were high under iron-depleted condition. Furthermore, the bioinformatics analysis showed that iron uptake receptors of FepA, FhuA, and IutA contain promising antigenic regions to elicit both humoral as well as cell-mediated immune responses. In addition, antigenicity analysis demonstrated that the recombinant proteins corresponding to FepA, FhuA, and IutA protein were antigenic against anti-Shigella group antigen-antibody and Shigellainfected human serum. The findings could impact the development of an effective vaccine against Shigella infection by the utilization of iron uptake receptors as part of vaccine formulation. However, the protective efficacy and the effectiveness of these proteins against shigellosis needs to be further evaluated through in vivo study.